Componentes da produtividade total de fatores e sua influência na desigualdade de renda dos países: 1960-2000 - Souza, Rogério César de (2005)
This study presents a new and alternative approach to the relation between economic growth and income distribution, from a Stochastic Frontier Analysis – SFA – perspective. First, the study analyses the effects of the evolution of total productivity of factors (TPF) and its components (technical efficiency, technological progress, scale and allocative efficiencies) on economic growth. Specifically, it assesses to what extension countries’ differences with respect to technological patterns of development influence their economic growth. Then, it compares the evolution of inequality in per capita income distribution between developed and developing countries and relates the obtained Theil’s L inequality measure to the TPF components, in order to show that there is no per capita income convergence between the two groups of countries. On the contrary, it shows that the technological gap between those two groups of countries has been enlarged along the years. Finally, it identifies the role of technological progress in the income distribution dynamics inside countries, restoring Kuznets founding idea that technological progress is the main motor of development. We conclude that the effects of the technological progress on the economies are more general than just the promotion of economic growth: it also enhances labor productivity, wages and, in consequence, reduces income inequality.